The structure of professional readiness of border guard inspectors to identify persons and vehicles - Tkachuk, Dmytro (Professional Pedagogics, 2018)
The article reveals the essence, structure and features of the content of the professional readiness of the border guard inspectors for the identification of persons and vehicles. It was revealed that this is a professionally important personal pecularity, covering the inspector’s attitude towards identification at checkpoints, as well as the knowledge of the technology, methods and means of identifying persons and vehicles, professional personal qualities and skills necessary for the proper implementation of this process at the state border checkpoints. In the structure of the professional readiness of the border guard inspectors three components are identified for the identification of persons and vehicles. The personal component based on value covers the professional value orientations of the serviceman of the State Border Guard Service, professional qualities (professional observation, memory, attentiveness, high performance and resistance to excessive tasks), professional orientation and motives of professional activity. The cognitive component covers the subject (gabitoscopy, the theory of identification) and special (organization and implementation of identification at checkpoints) knowledge. The activity component covers a set of skills necessary for the organization and implementation of identification of persons and vehicles at checkpoints.